Exploring Emotional Intelligence in a Caribbean Medical School - Sa, B (West Indian Med J, 2014)
OBJECTIVE: To explore the emotional intelligence (EI) in medical students in a Caribbean medical school and investigate its association with gender, age, year of study and ethnicity. DESIGN AND METHODS: A cross-sectional design using convenient sampling of 304 years two to five undergraduate medical students at the School of Medicine, The University of the West Indies (UWI), St Augustine campus, was conducted. The Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT-V2.0) was administered to test four branches of EI: perceiving emotions, facilitating thought, understanding emotions and managing emotions. Data were analysed using SPSS version 19. T-test, analysis of variance (ANOVA) and r (product moment correlation) were calculated to establish the effects of selected variables (gender, age, year of study and ethnicity) on total and sub-scales EI scores and tested against 0.05 and 0.01 significance levels. RESULTS: The total mean score for EI fell within the average according to MSCEIT standards. Gender analysis showed significantly higher scores for males and for younger age groups (< 25 years). Year of study and ethnicity did not yield any significant effect. CONCLUSIONS: These findings of higher EI scores in males and younger students are unusual, given the well-publicized stereotype of the Caribbean male and the perception that advancing age brings maturity and emotional stability. It would be valuable to widen this study by including other UWI campuses and offshore medical schools in the Caribbean. This preliminary study examined a sample of medical students from a well-established Caribbean medical school. Since EI is considered to be important in the assessment and training of medical undergraduates, consideration should be given to introducing interventions aimed at increasing EI.